ANALISIS KESALAHAN SISWA MENGOPERASIKAN PECAHAN ALJABAR - Patmawati; Hamidah Suryani Lukman; Ana Setiani (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2022)
The problem of students' difficulty understanding algebraic material can trigger errors when solving problems of algebraic forms. The purpose of this study was to determine the types of errors, the factors that cause student errors in solving algebraic fraction operations, to prevent students from making the same mistakes when completing algebraic fraction operations. The method in this study is a qualitative descriptive method, with the type of research being Case Studies. This research was conducted at SMPN 1 Cikembar class VII who had studied the material of algebraic fractions. Students selected as many as 3 students based on certain considerations. The data collection of this research was carried out by the method of tests and interviews. Meanwhile, data analysis and data reduction include data selection, data presentation and drawing conclusions. To test the validity of this research data using source triangulation. Based on the results of data analysis, it can be concluded that the types of student errors in operating algebraic fractions include (1) Error in writing formula (2) Incorrect error using the formula (3) Error in equating both sides with the same number (4) Error substituting the value into in the variable (5) Error operating similar terms (6) Error not equating the denominator first (7) error writing number sign (8) irregular step error in solving problems (9) Error not continuing the solution. The factors that cause students' errors in operating algebraic fractions include (1) not understanding the questions well (2) not mastering the prerequisite material (3) not mastering the concept of algebraic fraction operations (4) not being careful in reading questions (5) student habits in solving problems (6) are not yet skilled in manipulating algebraic fractions.